Exploring the importance of sulfate transporters and ATP sulphurylases for selenium hyperaccumulation—a comparison of Stanleya pinnata and Brassica juncea (Brassicaceae) - Schiavon, Michela; Pilon, Marinus; Malagoli, Mario; Pilon-Smits, Elizabeth A. H. (Frontiers in Plant Science, 2015)
Selenium (Se) hyperaccumulation, the capacity of some species to concentrate Se to levels upwards of 0.1% of dry weight, is an intriguing phenomenon that is only partially understood. Questions that remain to be answered are: do hyperaccumulators have one or more Se-specific transporters? How are these regulated by Se and sulphur (S)? In this study, hyperaccumulator Stanleya pinnata was compared with related non-hyperaccumulator Brassica juncea with respect to S-dependent selenate uptake and translocation, as well as for the expression levels of three sulphate/selenate transporters (Sultr) and three ATP sulphurylases (APS). Selenium accumulation went down ~10 fold with increasing sulphate supply in B. juncea, while S. pinnata only had a 2-3 fold difference in Se uptake between the highest (5 mM) and lowest sulphate (0 mM) treatments. The Se/S ratio was generally higher in the hyperaccumulator than the non-hyperaccumulator, and while tissue Se/S ratio in B. juncea largely reflected the ratio in the growth medium, S. pinnata enriched itself up to 5-fold with Se relative to S. The transcript levels of Sultr1;2 and 2;1 and APS1, 2 and 4 were generally much higher in S. pinnata than B. juncea, and the species showed differential transcript responses to S and Se supply. These results indicate that S. pinnata has at least one transporter with significant selenate specificity over sulphate. Also, the hyperaccumulator has elevated expression levels of several sulphate/selenate transporters and APS enzymes, which likely contribute to the Se hyperaccumulation and hypertolerance phenotype.